Synthesis of ZnO-Cu-C yolk-shell hybrid microspheres with enhanced electrochemical properties for lithium ion battery anodes. (1st February 2017) - Xie, Qingshui; Lin, Liang; Ma, Yating; Zeng, Deqian; Yang, Jingren; Huang, Jian; Wang, Laisen; Peng, Dong-Liang
Graphical abstract: Highlights: ZnO-Cu-C yolk-shell hybrid microspheres are prepared by a facile approach. Yolk-shell hybrids show greatly strengthened lithium storage properties. The notable battery properties of hybrids are due to their yolk-shell structures, Cu and C decoration. Abstract: Zinc-copper citrate porous, yolk-shell and hollow microspheres are controllably produced via a facile electrostatic interplay between zinc citrate solid microspheres and copper sulphate solution with controllable concentration. By calcination of the firstly acquired zinc-copper citrate precursors in inert atmosphere, the corresponding ZnO-Cu-C porous, yolk-shell and hollow hybrid microspheres are synthesized. When adopted as the electrode materials for lithium ion batteries, the produced ZnO-Cu-C yolk-shell hybrid microspheres depict higher reversible capacity and better cycling stability than ZnO-Cu-C porous hybrid microspheres. After 500 cycles at 200 mA g −1, yolk-shell hybrids deliver a reversible capacity of 769 mA h g −1 . Additionally, ZnO-Cu-C hollow hybrid microspheres exhibit best rate capability, which is due to their special three dimensional Cu conductive network.